Characterizing the Relationship Between Neutralization Sensitivity and env Gene Diversity During ART Suppression - Wilson, Andrew; Shakhtour, Leyn; Ward, Adam; Ren, Yanqin; Recarey, Melina; Stevenson, Eva; Korom, Maria; Kovacs, Colin; Benko, Erika; Jones, R. Brad; Lynch, Rebecca M. (Frontiers in Immunology, 2021)
Although antiretroviral therapy (ART) successfully suppresses HIV-1 replication, ART-treated individuals must maintain therapy to avoid rebound from an integrated viral reservoir. Strategies to limit or clear this reservoir are urgently needed. Individuals infected for longer periods prior to ART appear to harbor more genetically diverse virus, but the roles of duration of infection and viral diversity in the humoral immune response remain to be studied. We aim to clarify a role, if any, for autologous and heterologous antibodies in multi-pronged approaches to clearing infection. We characterized the breadths and potencies of antibody responses in individuals with varying durations of infection and HIV-1 envelope (env) gene diversity as well as the sensitivity of their inducible virus reservoir to broadly neutralizing antibodies (bNAbs). Plasma was collected from 8 well-characterized HIV-1+ males on ART with varied durations of active infection. HIV envs from reservoir-derived outgrowth viruses were amplified and single genome sequenced in order to measure genetic diversity in each participant. IgG from plasma was analyzed for binding titers against gp41 and gp120 proteins, and for neutralizing titers against a global HIV-1 reference panel as well as autologous outgrowth viruses. The sensitivity to bNAbs of these same autologous viruses was measured. Overall, we observed that both a longer duration of infection and greater env diversity were associated with higher neutralizing titers against the global panel. Higher env gene diversity within inducible virus was also associated with increased resistance to bNAbs. Despite anti-HIV-1 antibody titers, we did not observe potent neutralization against autologous viruses.That this lack of neutralization was observed regardless of infection duration and viral diversity suggests that the inducible reservoir harbors ‘escaped’ viruses (that co-evolved with autologous antibody responses), rather than proviruses archived from earlier in infection. Finally, we observed that viruses resistant to autologous neutralization remained sensitive to bNAbs. Overall, our data suggest that the inducible reservoir is relatively resistant to autologous antibodies and that individuals who start ART early in infection, and so develop limited virus variation in the env gene, are more likely to be sensitive to bNAb treatment.